Corporate governance, political connection, and foreign ownership control: The property rights theory perspective - Pranesti, Arin; Fajar, Muhammad Andryzal; Larasati, Kharisma Saski; Widiyanti, Arsy (JIFA (Journal of Islamic Finance and Accounting), 2022)
Over time, the reduction in foreign ownership in Indonesia has prompted questions about its causes. The country is still perceived to have low corporate governance standards and a high level of political connections. The aim of this study is to investigate whether corporate governance and political connections have an impact on foreign ownership. The study utilized manufacturing company data from 2018 to 2021, comprising 48 companies with 192 observations. The findings of the study indicate that foreign investors tend to decrease their investment in companies with strong corporate governance. The study reveals that a firm with robust corporate governance becomes an attractive target for local investors to acquire ownership. The findings provide evidence of a decrease in the proportion of foreign investors in such companies. Instead, foreign investors continue to view companies with political connections as potential concern for surveillance. This study uses another argument to explain how the structure of foreign ownership in Indonesia uses the property right theory. Policy-making authorities can make policies to support corporate governance arrangements and support to reduce the level of corruption so as to support the investment climate in Indonesia. This research can be used as a new insight to understand how the investment climate is, but has not considered aspects related to environmental and social issues